Ecuador : First Review Under the Stand-By Arrangement and Requests for Modifications and Waiver of Nonobservance and Applicability of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2003)
Output growth, inflation, and the external current account balance are the major economic developments discussed in this study. The macroeconomic framework was modified to reflect recent information. The reforms in the banking system are helpful in completing the process of dealing with the failed banks. The authorities are contacting international financial experts to manage the debt reductions. Finally, the central government will need to be vigilant in implementing its challenging financing program. The program contains several prior actions to complete the first review.